Diseño en EES de un intercambiador de calor pirotubular para un horno panelero (2020)
This paper presents the design process in the EES software of a pyro-tubular heat exchanger focused on the panela industry. This type of heat exchanger is a further step in search for improving heat transfer in the panela production processes, since this industry is currently experiencing a problem associated with energy deficiencies. The proposed heat exchanger is 244 cm long x 122 cm wide (in the narrowest section). It has 3 pyrotubes of 20 cm internal diameter and 244 cm in length, evenly distributed over the width of the heat exchanger. Pyrotubes are made of 12-gauge stainless steel. Considering the dimensions proposed for the heat exchanger, and assuming boundary conditions based on the current operating data: juice volume of 1.012 m^3, mass of combustion gases of 0.7603 kg/s and a gas inlet temperature of 796 K, the total heat transferred from the combustion gases flowing internally through the tubes to the water, the gas outlet temperature, and the evaporated water ratio in an operating cycle were calculated.--Taken from the Degree Document Format.